(untitled) (Research, Society and Development, 2021)
The production of quality seedlings is related to the level of efficiency of the substrates, being essential in planting perennial fruit trees, as is the case of the bacabi palm (O. mapora). However, there is a lack of studies to determine the ideal substrate and its efficiency in bacabi seedling production. The objective of this work was to evaluate organic substrates in the development of seedlings of this specie. We used seedlings obtained from seeds collected at the Oenocarpus germplasm bank of Embrapa Eastern Amazon. The seedlings were transplanted to black bags containing three substrates: 100% soil, 75% soil + 25% bovine manure and 60% soil + 40% poultry litter. The design used was entirely random with three treatments and 20 repetitions with one seedling plot. During the twelve-month period, the following were evaluated monthly: total number of leaves (TNL), number of emitted leaves (NEL), diameter of the stalk (DS), survival rate (%), fresh matter of the aerial part (FMAP) and root system (FMRS) and dry matter of the aerial part (DMAP) and root system (DMRS). The characters were submitted to variance analysis and Tukey test (p≤ 0.05). The substrates differed for at least one of the characters in six evaluations. The highest means were recorded on the substrates compost and compost+bovine manure, especially for the characters TNL and DS. For FMAP, FMRS, DMAP, and DMRS, the best substrate was terracing+stink. Therefore, the substrate soil+bovine manure promotes the best development of bacabi seedlings.